Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3758/mc.37.6.880
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and suppression effects resulting from information structuring in sentences

Abstract: 880The relative importance of particular parts of a sentence is signaled through devices of information structuring and prosodic stress, which control the focus of information within sentences, as is made clear in an extensive linguistic literature (see, e.g., Gundel, 1999;Halliday, 1967;Jackendoff, 1972;Rooth, 1992). In the present article, our interest is in the cognitive effects of linguistic prominence, which can be manipulated through information structuring devices, such as the it-cleft construction. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Focused information is processed deeper and remembered better than non-focused information [16][18]. Additionally, the phoneme of focused information is detected quicker than that of non-focused information, and the change of focused information is more likely to be detected than that of non-focused information [16], [17], [19], [20]. Third, contrastive focus can guide the processing of syntax ambiguities.…”
Section: Introductionmentioning
confidence: 99%
“…Focused information is processed deeper and remembered better than non-focused information [16][18]. Additionally, the phoneme of focused information is detected quicker than that of non-focused information, and the change of focused information is more likely to be detected than that of non-focused information [16], [17], [19], [20]. Third, contrastive focus can guide the processing of syntax ambiguities.…”
Section: Introductionmentioning
confidence: 99%
“…There is ample evidence that syntactically prominent information is more readily accessible in memory than non-prominent information (Birch, Albrecht, & Myers, 2000; Birch & Garnsey, 1995; Birch & Rayner, 2010; Sanford, Price, & Sanford, 2009; Sturt, Sanford, Stewart, & Dawydiak, 2004; Ward & Sturt, 2007). However, while this increased accessibility facilitates pronoun processing (McKoon, Ward, Ratcliff, & Sproat, 1993; Sanford et al, 2009), its effect on the processing of repeated-name anaphors is less straightforward.…”
mentioning
confidence: 99%
“…However, while this increased accessibility facilitates pronoun processing (McKoon, Ward, Ratcliff, & Sproat, 1993; Sanford et al, 2009), its effect on the processing of repeated-name anaphors is less straightforward. When a repeated name refers to a syntactically prominent antecedent, coreferential processing appears to be impaired.…”
mentioning
confidence: 99%
“…In addition, Cutler and Fodor (1979) found that the reaction time to detect a phoneme target in the answer sentence was faster when the target phoneme occurred in focused words. Moreover, Sanford et al (2009) found that the use of cleft sentences increases the processing efficiency of references. The difference in processing focused and non-focused information implies that IS modulates language processing by allocating more attentional resources to the focused than non-focused information, and hence the focused information obtains deeper processing.…”
Section: The Influence Of Is On Depth Of Language Processingmentioning
confidence: 99%